1, 1′‐Bis(thymine)ferrocene Nucleoside: Synthesis and Study of Its Stereoselective Formation. Issue 6 (13th June 2017) - Anisimov, Iurii; Saloman, Sebastian; Hildebrandt, Alexander; Lang, Heinrich; Trzybiński, Damian; Woźniak, Krzysztof; Šakić, Davor; Vrček, Valerije; Kowalski, Konrad
Abstract: The synthesis of 1, 1′‐bis(thymine)ferrocene nucleoside is reported. This nucleoside was obtained in a two‐step synthetic methodology including a Michael addition reaction of 1, 1′‐bis(3‐chloropropionyl)ferrocene with thymine to afford the bis(thymine) adduct in 44 % yield. In the second step, the two prochiral carbonyl functionalities in the Michael adduct were reduced to hydroxyl groups with sodium borohydride. This apparently straightforward reaction proceeds in a highly stereoselective fashion to yield the title ferrocenyl nucleoside as a racemic mixture that consists of the R, R and the S, S isomers. The absolute configuration of the chiral carbon atoms in the nucleoside was assigned on the basis of single‐crystal X‐ray diffraction analysis of the methyl derivative. Furthermore, the mechanism of reduction of the bis(thymine) adduct was investigated by using DFT calculations. The two critical minima, pre‐reactive complex, and semi‐reduced intermediate, as well as two corresponding transition states were located to support the observed stereoselectivity. The redox properties of 1, 1′‐bis(thymine)ferrocene nucleoside, its precursor, and congeners were investigated using cyclic voltammetry. For the title compound a reversible redox process was found at a low potential of −30 mV versus FcH/FcH + (FcH=Fe(η 5 ‐C5 H5 )2 ) as the reference redox couple. Abstract : Choosing nucleosides : An artificial ferrocenyl nucleoside (see figure) was obtained as a racemic mixture, studied with cyclic voltammetry, and transformed into a per‐methylated derivative suitable for X‐ray diffraction analysis. The stereochemical outcome of nucleoside formation was investigated by means of DFT calculations.